Pemodelan Penduduk Miskin di Provinsi Maluku Dengan Menggunakan Metode Backward - Salmon N. Aulele; Henry W. M. Patty (Program Studi Statistika FMIPA Universitas Mulawarman, 2017)
Poverty is a complex issue, for it is not only related to the low level of income and consumption, but also to the low level of education, health and powerlessness to participate in development as well as various issues that are relevant to human development. According to the Badan Pusat Statistik (BPS), poverty is the inability to meet certain standards of basic needs, both food and non-food. The results of BPS survey on March 2017 showed that Maluku Province is ranked 4th in the poorest province in Indonesia with a poverty percentage of 18.45% of the total population in Maluku. This study aims to analyze the number of poor people in Maluku and its affecting variables by using backward method. The results show that Southwest Maluku Regency has the highest percentage of poor people in Maluku 31.01% and Ambon City has the lowest percentage of poor people with 4.64% of the poor. While the significant variables which affecting the percentage of poor people in Maluku are the percentage of households whose fuel for cooking is from wood; the percentage of population aged 7-24 years who is not / has never attended school; the percentage of population aged 7-24 years no longer schooling; the percentage of open unemployment rate; and the percentage of labor force participation rate per Regency/City in Maluku.